Reimagining Leadership: A Hamka’s Perspective on Women’s Role in Power - Abdulfatah, Fikri; Akmala, Minhatu (Taqaddumi: Journal of Quran and Hadith Studies, 2024)
This research aims to delve into the perspectives of Haji Abdul Malik Karim Amrullah (Hamka) concerning the role of women in Islamic leadership. Through a qualitative analysis of the Tafsir al-Azhar, this study reveals that Hamka emphasised the significance of justice, integrity, and consultation as the foundations of leadership, regardless of gender. By analysing various verses, interpretations, and written works on his thoughts, this research identifies several inclusive leadership principles within Hamka's thinking, such as the principle of prioritising the collective good over individual interests. These findings suggest that Hamka opened up opportunities for women to play a more active role in leadership, challenging patriarchal norms that restrict women's potential. This research is anticipated to contribute to the development of a more inclusive framework for Islamic leadership and to foster efforts to empower women in various fields, including politics and religion.